Offending and victimization in prisons: new theoretical and empirical approaches - Ginneken, Esther F. J. C. van (International journal of law, crime and justice, 2024)
In-prison offending and victimization threaten the safety of incarcerated individuals and staff, which makes it an important topic for correctional research. Prior research has generated substantial knowledge about individual and environmental characteristics that heighten the risk of in-prison offending and victimization. The victim-offender overlap and the situational dynamics of incidents, however, are still under-researched. This essay proposes that the study of in-prison offending and victimization would benefit from adoption of an incident-level approach. This recognizes that incidents can escalate and de-escalate depending on persons involved and their (re)actions, and that victimization and offending are often linked. It is discussed how criminological theories and methods on crime and victimization outside prisons can be adapted for this purpose.